Entrepreneurship Perspective for Trade and Management of Horticulture Sector in Kashmir Himalayan Valley - Hanan, Ebtisam (International Journal of Social Sciences and Management, 2015)
Horticulture sector plays an extremely important role in trade and economy of Jammu and Kashmir State, India. Productivity and export of horticultural produce are vital for supplementing farm income and overall employment in the agricultural sector. J&K State, renowned for its diverse fruits supports more than 5 lac families, and plays an important role (directly or indirectly) in the employment of nearly 25 lac people annually. Survey reports indicate that about 2.175 lac ha is under fruit crops with prospectus of bringing 1.70 lac ha more under fruit plantation crops. Apple has distinction of being principal fruit crop of the state in terms of production, and accounts for about 60-65 % of the total area of 2.95 lac hectares under all temperate fruits. Horticultural production systems hold promising and flourishing trade prospects for enthusiastic entrepreneurs, and as such warrant intense structural changes through diversification, value addition, harmonious integration of modern and indigenous know-how, organized marketing strategies and infrastructure development for the sustainable production of fruits and their processed products. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 284-289 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12986